Additional Thoughts on the Medieval 'Cornish Bible'. (1st May 2006) - Spriggs, Matthew
An interesting feature of recent debate about the Cornish language is the discussion concerning evidence for the existence (or otherwise) of a medieval 'Cornish Bible'. This article revisits Malte Tschirschky's refutation, voiced in Cornish Studies: Eleven (2003), of the 'evidence' presented by Charles Penglase to support his view that John Tregear must have had access to a Middle Cornish translation of the Bible when compiling his Homilies c.1555-58. Penglase has not produced any corroborating evidence to give credence to his claims, but this does not mean that evidence cannot be found. This article returns to such evidence to ensure the 'proper hearing' it deserves, sifting through a range of contemporary material, including that of the seventeenth- and eighteenth-century Cornish language enthusiasts. None of this yet proves the existence of a medieval Cornish Bible, however '[l]ike Tschirschy, I too would also be delighted to be proved wrong . . . [t]he discovery of Beunans Ke and the reappearance of several other notable Cornish language works in recent years gives us hope that more may yet be found.'